Proses Berpikir Mahasiswa dalam Memecahkan Masalah Fungsi Pembangkit - Mutianingsih, Ninik; Prayitno, Lydia Lia; Kurniawan, Agus Prasetyo (UIN Sunan Ampel Surabaya, 2018)
This study aims to describe studentsâ thinking process in solving the problems of generating function. This is a case study that classifies students into three categories: high, medium, and low. Subjects were asked to solve the problems then use think aloud to reveal their thinking process. The results show that in understanding the problem, using conceptual and procedural knowledge related to the problems, strategies, and experiences they have in solving similar problems between the three subjects is different. Subjects with high and medium capability are able to reveal the problem-solving component of Polya in detail, whereas low-ability subjects use only some of the problem-solving components of Polya.